The Use of Hangman Game in Motivating Students in Learning English - Manan, Rika Mandasari (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
In learning foreign language such as English, a learner should have motivationin  order  to  have  willingness  to  learn.  This  study  is  an  attempt  to  investigate  thestudents’ motivation in learning English by using Hangman Game. And this study wasto find out if the use of Hangman game motivates the students in learning English. Themethod  used  in  this  study  was  quantitative  with  experimental  research  design.  Thetarget population of this study was the eighth grade students of MTs Negeri Cirebon 1.The writer took two classes as samples and the number of the samples was 36 students.The  samples  were  divided  into  experimental  group  and  control  group.  There  are  tworesearch  instruments  which  were  used  to  collect  data.  They  were  questionnaire  andobservation. The result analysis of observation showed that the students in experimentalgroup  had  higher  motivation  than  in  control  group.  Meanwhile,  the  calculation  of  thevalue  of  the  questionnaire  showed  that  there  were  significant  differences  betweenexperimental group and control group. The result of taccount was 2,44 while the result ofttable was  1,994.  It  was  mean  that  the  value  of  taccount (2,44)  >  ttable (1,994).  So,hypotheses  alternative  (Ha)  was  accepted  or  the  use  of  Hangman  game  motivate  thestudents in learning English to eighth grade students of MTs Negeri Cirebon 1.